Nucleosomal array condensation: new insights into an old "tail" - Sorensen, Troy C., author; Hansen, Jeffrey C., advisor; Stargell, Laurie, committee member; Luger, Karolin, committee member; Bailey, Susan, committee member (Colorado State University. Libraries, 2011)
The DNA present within the nucleus of each human somatic cell, when extended end to end, would span a distance of about one meter. The first level of compaction critical to fitting the entire genome into the nucleus is the nucleosome, consisting of 147 base pairs of DNA wrapped 1.7 times around an octameric structure composed of the four core histones H2A, H2B, H3 and H4. Nucleosomes separated by up to 80 base pairs of linker DNA called nucleosomal arrays compact the DNA further through short range intra-array and long range inter-array contacts that generate different levels of higher order condensed structures. This dissertation investigates the involvement of the core histone "tail" domains as well as the influence of the H3 centromeric variant CENP-A in nucleosomal array condensation events. In vitro, 12-mer nucleosomal arrays condense intra- and inter-molecularly through nucleosome-nucleosome interactions driven primarily by the core histone tail. This dissertation details the contributions and the molecular determinants of the histone tail domains to the condensation processes. Importantly, we found that the H3 and H4 tail domains were the largest contributors to array condensation. The mode of action used by the H4 tail domain in intra- and intermolecular condensation centered on the following determinants: 1) position of the H4 tail, 2) amino acid composition, 3) positive charge density and 4) tail domain length. Importantly, the primary sequence of the H4 tail was found to not be an important molecular determinant. To date no study has been performed to determine short-range compaction between "bulk" H3 containing and H3 centromeric specific variant, CENP-A chromatin. 12-mer nucleosomal arrays containing either H3 or CENP-A histones were reconstituted and tested for their ability to fold intra-molecularly. Major finding include that CENP-A containing nucleosomal arrays assemble in the same stepwise manner as conical arrays and were always more compact than H3 containing arrays at every salt concentration tested. The increased compaction was found to be in part due to a lysine to arginine mutation at position 49 of CENP-A.
Keywords: CENP-A; nucleosomal array; H4 N-terminal domain; chromatin